Total Phenolics and Potential Antioxidant Activity in Natural Materials: Banana Stems and Bean Sprouts as Growth Regulators for Chilli Peppers (Capsicum frutescens L) - Pratama, Jovan; Anggarani, Mirwa Adiprahara (Jurnal Pijar Mipa, 2025)
Indonesia has abundant horticultural commodities, including chilli plants, which have high economic value. However, their productivity remains low at 8.35 tons/ha, compared to the potential 20–40 tons/ha. To boost the productivity of red cayenne pepper, additional supplements such as phytohormones auxin, gibberellin, and cytokinin are needed. This study uses natural sources of phytohormones derived from banana stems and mung bean sprouts. The aim is to measure the antioxidant activity and total phenolic content of various combinations of these natural plant growth regulators (PGRs) to support plant productivity. An experimental design was used, analyzing antioxidant activity using the DPPH method with IC50 values, and total phenolics using the Folin-Ciocalteu method. Six variations were tested: A (banana stem extract 10:0), B (banana stem:bean sprouts 8:2), C (6:4), D (4:6), E (2:8), and F (bean sprout extract 10:0). Antioxidant activity and total phenolics were measured using a UV-Vis spectrophotometer. The results showed that variation C (6:4) had the highest total phenolic content (8.8 mg GAE/g) and an IC50 value of 210 ppm, indicating moderate antioxidant activity. These findings suggest that the combination of banana stem and bean sprout extracts in the right proportion can enhance the functional properties of natural PGRs, potentially supporting the growth and productivity of red cayenne pepper plants.